A Systematic Review of International Affective Picture System (IAPS) around the World - Diogo Branco; Óscar F. Gonçalves; Sergi Bermúdez i Badia (Sensors, 2023)
Standardized Emotion Elicitation Databases (SEEDs) allow studying emotions in laboratory settings by replicating real-life emotions in a controlled environment. The International Affective Pictures System (IAPS), containing 1182 coloured images as stimuli, is arguably the most popular SEED. Since its introduction, multiple countries and cultures have validated this SEED, making its adoption on the study of emotion a worldwide success. For this review, 69 studies were included. Results focus on the discussion of validation processes by combining self-report and physiological data (Skin Conductance Level, Heart Rate Variability and Electroencephalography) and self-report only. Cross-age, cross-cultural and sex differences are discussed. Overall, IAPS is a robust instrument for emotion elicitation around the world.